2013
DOI: 10.1002/lary.24132
|View full text |Cite
|
Sign up to set email alerts
|

Postdeglutitive residue in idiopathic unilateral vocal fold paralysis

Abstract: Idiopathic UVFP patients were more likely to demonstrate increased residue and asymmetry toward the involved region as compared with RLNP patients, suggesting that nerve involvement in idiopathic UVFP may not be exclusive to the RLN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…The characteristics of articles that met inclusion criteria are displayed in Table 2. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] The prevalence of symptomatic dysphagia among patients with UVFI, as identified by self-reporting or clinical evaluation, was 55.6% to 69.0%. In studies that identified swallowing dysfunction mechanistically through videofluoroscopic swallowing study (VFSS) or functional endoscopic evaluation of swallowing (FEES), the aspiration rate ranged from 20.0% to 50.0%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The characteristics of articles that met inclusion criteria are displayed in Table 2. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] The prevalence of symptomatic dysphagia among patients with UVFI, as identified by self-reporting or clinical evaluation, was 55.6% to 69.0%. In studies that identified swallowing dysfunction mechanistically through videofluoroscopic swallowing study (VFSS) or functional endoscopic evaluation of swallowing (FEES), the aspiration rate ranged from 20.0% to 50.0%.…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies reported UVFI laterality, and with the exception of Fang et al, the majority of injuries were left-sided. 8,9,[11][12][13][14][15][16][17][18]20,21 Although left UVFI occurred more frequently, there was no significant difference in the Penetration-Aspiration Scale (PAS) score and no increased risk of aspiration between right and left immobility. 12,15 UVFI etiologies are categorized in Table 3 as iatrogenic (6.7%-68.0%), noniatrogenic trauma (3.1%-26.7%), neoplasm (3.6%-47.4%), medical disease (4.2%-29.6%), mechanical (4.2%), and idiopathic (6.3%-60.6%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 The affected vallecula of Group I did not demonstrate significantly increased residue compared to the non-affected side (a), and the same comparison in Group II also did not demonstrate any significant difference (b). Compared to Group II, Group I did not have significantly more residue on the vallecula of the affected or non-affected side group previously demonstrated that idiopathic UVFP patients are more likely to demonstrate increased residue and asymmetry towards the involved pharyngeal region compared to patients with isolated RLNP [13]. This suggests that the nerve involvement in idiopathic UVFP is more extensive compared to patients with vagus or superior laryngeal nerve paralysis, because it is not limited to the RLN.…”
Section: Discussionmentioning
confidence: 53%
“…With respect to this limitation, we validated the quantitative measurement of the area outlined in the lateral view of the VFSS still image by calculating inter-and intra-rater correlation coefficients, which were all found to be in the excellent range (0.88-0.92), demonstrating a high consistency and stability in the evaluation. In addition, we previously verified this method [13].…”
Section: Discussionmentioning
confidence: 80%